Perlindungan Hukum terhadap Pemegang Hak atas Tanah dalam Pelaksanaan Ganti Kerugian Pengadaan Tanah bagi Pembangunan untuk Kepentingan Umum (Studi Putusan Nomor: 95/Pdt.G/2021/Pn.Kis) - Febiola SIburian (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the forms of legal protection for land rights holders in the context of land acquisition for public interest, and to launch its implementation through a case study of Decision Number 95/Pdt.G/2021/PN.Kis. The phenomenon studied was caused by problems between the government as the implementer of development projects and the community as landowners, who often suffered losses in the compensation process. The research method used was normative juridical with a regulatory, case, and conceptualization approach. The results of the study indicate that in this case, there were administrative errors in the form of errors in the object of land valuation and the failure to carry out proper compensation deliberations. This contradicts the principles of justice, participation, and legal certainty as stipulated in Law Number 2 of 2012. The panel of judges declared this action to be an unlawful act and partially granted the plaintiff's claim. These findings indicate that legal protection is still not optimal and that there is a need for strengthening regulations and supervision in the implementation of land acquisition to prevent harm to the community.